Copper(i)oxide microparticles – synthesis and antimicrobial finishing of textiles1. Issue 28 (28th July 2015) - Turalija, M.; Merschak, P.; Redl, B.; Griesser, U.; Duelli, H.; Bechtold, T.
<x xml:space="preserve">Abstract</x> Copper(i)oxide microparticles were be bound to textile surfaces by means of a pigment binder system to provide antibacterial activity with good wash permanence, using rather simple processing and ordinary chemicals.